1985
DOI: 10.1111/j.1471-4159.1985.tb07155.x
|View full text |Cite
|
Sign up to set email alerts
|

[3H]8‐Hydroxy‐2‐(Di‐n‐Propylamino)Tetralin Binding to Pre‐ and Postsynaptic 5‐Hydroxytryptamine Sites in Various Regions of the Rat Brain

Abstract: The specific binding of [3H]8-hydroxy-2-(di-n-propylamino)tetralin ([ 3H]8-OH-DPAT) to 5-hydroxytryptamine (5-HT)-related sites was investigated in several regions of the rat brain. Marked differences were observed in the characteristics of binding to membranes from hippocampus, striatum, and cerebral cortex. Hippocampal sites exhibited the highest affinity (KD approximately 2 nM) followed by the cerebral cortex (KD approximately 6 nM) and the striatum (KD approximately 10 nM). Ascorbic acid inhibited specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
137
1

Year Published

1992
1992
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 470 publications
(149 citation statements)
references
References 29 publications
11
137
1
Order By: Relevance
“…After incubation for 30 miu, the contents were centrifuged at 100,000 X g for 1 h. The clear supernatant was carefully removed from the pellet, and either used immediately for binding assay or for PEG precipitation. PEG precipitation of the crude CHAPS extract was performed to remove NaC1 from the solubilized extract since the agonist binding of 5-HT]A receptor is inhibited by NaC1 [18]. This procedure is believed to remove the salt [19,20].…”
Section: Methodsmentioning
confidence: 99%
“…After incubation for 30 miu, the contents were centrifuged at 100,000 X g for 1 h. The clear supernatant was carefully removed from the pellet, and either used immediately for binding assay or for PEG precipitation. PEG precipitation of the crude CHAPS extract was performed to remove NaC1 from the solubilized extract since the agonist binding of 5-HT]A receptor is inhibited by NaC1 [18]. This procedure is believed to remove the salt [19,20].…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, dissociation of the ligand was rapid and 85% of specifically bound [3H]-8-OH-DPAT dissociated within 10 min. Since the ionic conditions employed in the binding assays (50 mm Tris-HCl; Hall et al, 1985) were considerably different from those used in electrophysiology experiments, it cannot yet be excluded that the dissociation rate constant for 8-OH-DPAT (and the other synthetic ligands) is indeed very slow under conventional in vitro conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Radioligand binding experiments with [3H]-8-OH-DPAT (Hall et al, 1985) showed that binding to hippocampal and striatal membranes reached equilibrium within 5-7 min, which might explain the slow onset of hyperpolarization. In contrast, dissociation of the ligand was rapid and 85% of specifically bound [3H]-8-OH-DPAT dissociated within 10 min.…”
Section: Discussionmentioning
confidence: 99%
“…Aghajanian's group showed that autoregulation of firing was mediated by 5-HTreceptors on the 5-HT neurons [5][6][7]. Using the selective agonist 8-hydroxy-2-(di-n-propylamino) tetralin (8-OH-DPAT), Hamon's group identified the 5-HT 1A receptor as the major autoreceptor on the cell body and dendrites of 5-HT neurons of the raphe nuclei [8][9][10][11]. The 5-HT 1A autoreceptor was then shown to mediate 5-HT auto-inhibition [7,12].…”
Section: -Ht 1a Autoreceptors As Brakes For 5-ht Neurotransmissionmentioning
confidence: 99%